PENGARUH SOFT SKILL PENDIDIK DAN EFIKASI DIRI TERHADAP STRES AKADEMIK SISWA MADRASAH ALIYAH NEGERI KABUPATEN SEMARANG - Noor Miyono; Muhdi Muhdi; Ngurah Ayu Nyoman; Tri Wuryani (Jurnal SMART (Studi Masyarakat, Religi, dan Tradisi), 2019)
Academic stress is a condition in the form of physical, mental or emotional disorders caused by an incompatibility between the demands of environment and the actual resources of students so that they are increasingly burdened with various pressures and demands at school. The main objective of this study is to obtain empirical evidence on educator’s soft skills and student’s self-efficacy which led to student’s academic stress at State Islamic Senior High School (MAN) Tengaran of Semarang Regency. Population and sample of this study are XII grade student. The research sample of 125 respondents is determined by using quota random sampling. Data analysis technique uses regression analysis with the SPSS program (Statistical Package for Social Sciences) version 21.0. Based on the research data processing, the results of the study are as follows (1) educators’ soft skills have a significant effect on the students’ academic stress of 42,1% (2) self-efficacy has a significant effect on students’ academic stress of 49,5%. (3) educators’ soft skills and self-efficacy have a significant effect on students’ academic stress of 56,7%. While suggestion is (1) educators should continue to improve communication and social interaction with students so that they can carry out their activities happily without any coercion (2) educators must be more proactive in motivating students and building students’ confidence so they can rise in overcome their learning problems.